Comunidades arbóreas de dois reflorestamentos no município de Bebedouro, SP: composição, estrutura, diversidade funcional e representatividade regional - Barbosa, Mariana Zucoloto de Oliveira Guimarães [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The restoration of degraded areas is an extremely important process that seeks to assist and recover the ecological integrity of these areas, supporting the ecosystem to have sufficient biotic and abiotic resources that provide the self-sustainability of the formed forest community. The objective of this work was to identify the tree species that compose two reforested areas in the municipality of Bebedouro, SP, and to evaluate the effectiveness of reforestation based on ecological analyzes of composition and similarity with relatively less altered tree communities. For this, standardized quantitative sampling was carried out in plots of reforestation, in order to obtain richness, diversity, equity and functional diversity. In addition, species lists were compiled from four forest fragments in the same region, studied in 2008 and 2009, to compare floristic similarity and beta diversity with reforestation. With this study, it was possible to verify that the richness, diversity, structure and ecological function of the shrub-tree extract of the reforested communities were very similar to each other, however, compared to the reference fragments, there is a clear difference in species richness due to intrinsic differences, which suggests a possible need for enrichment mainly with native species.

A restauração de áreas degradadas é um processo de extrema importância que busca assistir e recuperar a integridade ecológica dessas áreas, dando suporte para que o ecossistema tenha recursos bióticos e abióticos suficientes que proporcionem a autossustentação da comunidade florestal formada. O objetivo deste trabalho foi identificar as espécies arbóreas que compõem duas áreas reflorestadas no município de Bebedouro, SP, e avaliar a efetividade do reflorestamento a partir de análises ecológicas de composição e similaridade com comunidades arbóreas relativamente menos alteradas. Para isso, foram realizadas amostragens quantitativas padronizadas em parcelas dos reflorestamentos, para obtenção da riqueza, diversidade, equitabilidade e diversidade funcional. Além disso, foram compiladas as listas de espécies de quatro fragmentos florestais da mesma região, estudados em 2008 e 2009, para comparação da similaridade florística e diversidade beta com os reflorestamentos. Com este estudo foi possível verificar que a riqueza, diversidade, estrutura e função ecológica do extrato arbustivo-arbóreo das comunidades reflorestadas foram muito similares entre si, porém, em comparação com os fragmentos referência, há uma diferença nítida de riqueza de espécies devidas diferenças intrínsecas, o que sugere uma possível necessidade de enriquecimento principalmente com espécies nativas.
Tree communities of two reforestations in the municipality of Bebedouro, SP: composition, structure, functional diversity and regional representation
Keywords: Reforestation; Composition; Seasonal forest; Richness; Reflorestamento; Botânica; Biodiversidade Conservação; Ecologia vegetal; Ciências Biológicas